Outcomes of adults with congenital heart disease and pulmonary hypertension in the advanced pulmonary vasodilator era. A regional multicenter registry (RACCA). (25th November 2020) - Wals Rodriguez, A; Federero Fernandez, C; Rodriguez Puras, M.J; Garcia Orta, R; Moreno Escobar, E; Robledo Carmona, J; Gallego, P
Abstract:  : The objective of this study is to evaluate mortality, causes and risk factors of death in adults with congenital heart disease (ACHD) and PHT on Pulmonary vasodilator therapy (PVT). Methods: 170 cases with PHT were identified in RACCA (Left heart disease were excluded (n=20)). We examined mortality, causes of death and complications during a mean follow-up (FU) of 7.9+4.6 years. For each patient demographic data, shunt location, clinical PHT group and functional class (FC) were collected. In an unselected sample of 103 patients, O2Sat, NT-proBNP, right ventricle function (RV) and 6-minute-test (6min) were retrospectively reviewed at 2 data collection time points: evaluation at baseline and the most recent data preceding death or at last clinical visit. Survival was assessed with Kaplan-Meier curves and differences between groups using the log-rank test. To look for predictors of death, Cox regression analysis was performed. Results: Patients with PHT were predominantly women (61%), aged 45 years (IQR 33–58.5). The distribution of PHT group by underlying defects were 58 Eisenmenger (ES) (Complex 50%) and 45 non-ES (pretricuspid 46.7% (p=0, 0002). PHT-pretricuspid defects occurred more in women with unrepaired simple defects and at older ages. In the sample, 85% were commenced on therapy with PVT (5% on initial dual therapy). The treated patients presented worse functional situation, more desaturation of O2 and worse TAPSE. In the group of treatment, 53% required treatment escalation during the FU. Initially, 82% were in sinus rhythm, in FC I-II 53% and in FC III-IV 39%. 10% had moderate-severe RV dysfunction. At the last visit, 38% were on monotherapy, 40% on dual therapy and 22% on triple therapy. FC improved from III-IV to I-II in 35% and 79% remained in FC-I-II without clinical deterioration. The Δ6min was +53±72 mts in those patients alive at the end of FU, and −126±26 mts in exitus cases (p=0, 003), but O2 saturation did not change significantly. Over the FU, 29 patients died. The main cause of death was heart failure, followed by sudden death. The event-free survival was 84% at 5 years. Survival was significantly worst for patients presenting with arrhythmias and more advanced FC at initiation of PVT and for those who developed RV dysfunction over FU. At multivariate analysis, syndromic forms, pretricuspid shunt, non-ES physiology, PVT and monotherapy at baseline, FC III-IV and desaturation were independent predictors for death. Conclusions: Although a positive clinical response was observed, mortality of PHT in CHD under advanced PVT remains high at mid-term FU. Heart failure is the leading cause of death. In terms of mortality, non ES patients and pretricuspid shunts were less responsive to treatment than patients with ES. Our results may suggest that patients with more advanced disease at the initiation of therapies do not respond properly and support the need for early treatment and initial dual therapy. Funding Acknowledgement: Type of funding source: None